2020
DOI: 10.3390/genes11040460
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Phenotype-Driven Tool for Rare Mendelian Variant Prioritization: Benchmarking Exomiser on Real Patient Whole-Exome Data

Abstract: Next-generation sequencing has revolutionized rare disease diagnostics, but many patients remain without a molecular diagnosis, particularly because many candidate variants usually survive despite strict filtering. Exomiser was launched in 2014 as a Java tool that performs an integrative analysis of patients’ sequencing data and their phenotypes encoded with Human Phenotype Ontology (HPO) terms. It prioritizes variants by leveraging information on variant frequency, predicted pathogenicity, and gene-phenotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 96 publications
(147 reference statements)
4
40
0
Order By: Relevance
“…Fig. 3B), in agreement with previous reports [52]. These data show the importance of including all types of cases and causal variants in benchmarking to avoid overestimation of diagnostic performance in real-world clinical applications.…”
Section: Gem Ai Outperforms Variant Prioritization Approachessupporting
confidence: 92%
“…Fig. 3B), in agreement with previous reports [52]. These data show the importance of including all types of cases and causal variants in benchmarking to avoid overestimation of diagnostic performance in real-world clinical applications.…”
Section: Gem Ai Outperforms Variant Prioritization Approachessupporting
confidence: 92%
“…Access to panel-based genetic testing and next-generation sequencing of both mitochondrial and nuclear genomes has greatly increased the potential to achieve a molecular genetic diagnosis. However, owing to the number of candidate sequence variations often yielded when multiple genes are sequenced, rigorous phenotyping is still important for the interpretation of genetic variants [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Primarily retrospective studies suggested higher rates of relevant results, and we replicate similar success to these studies in our observed concordance among previously diagnosed cases. 7,30,38 Importantly, the vast majority of our patients were undiagnosed when entering the study. This allowed us to establish the utility of computationally assisted interpretation among prospective diverse rare disease patients, on a scale far beyond any previously assessed rare disease cohort.…”
Section: Discussionmentioning
confidence: 98%
“…Multiple machine-learning tools have emerged to balance the variant/locus characteristics in an attempt to systematically extract optimal candidate prioritization. 7 The integration of such tools in rare disease molecular analyses has been demonstrated by several centers primarily for small, selected cohorts. [8][9][10][11][12] The universal feature is the patient's phenotype coded through human phenotype ontology (HPO) terms as a basis for prioritization, followed by the deployment of variable ranking algorithms.…”
Section: Introductionmentioning
confidence: 99%